Increased paediatric presentations of severe diabetic ketoacidosis in an Australian tertiary centre during the COVID‐19 pandemic. Issue 1 (23rd October 2020) - Lawrence, C.; Seckold, R.; Smart, C.; King, B. R.; Howley, P.; Feltrin, R.; Smith, T. A.; Roy, R.; Lopez, P.
Abstract: Aims: To determine if the frequency of severe diabetic ketoacidosis at presentation of new‐onset type 1 diabetes to an Australian tertiary centre increased during the initial period of restrictions resulting from the COVID‐19 pandemic (March to May 2020). Methods: Data were collected on presentations of newly diagnosed type 1 diabetes as well as on all paediatric presentations to the emergency department of a tertiary centre between 2015 and 2020. Data from the period of initial COVID restrictions in Australia (March to May 2020) were compared to the period March to May of the previous 5 years (pre‐pandemic periods). Results: The number of new diagnoses of type 1 diabetes was comparable in the pandemic period and pre‐pandemic periods (11 in 2020 vs range 6–10 in 2015–2019). The frequency of severe diabetic ketoacidosis was significantly higher in the pandemic period compared to the pre‐pandemic periods (45% vs 5%; P <0.003), odds ratio 16.7 (95% CI 2.0, 194.7). The overall frequency of diabetic ketoacidosis was also significantly higher during the pandemic period (73% vs 26%; P <0.007), odds ratio 7.5 (95% CI 1.7, 33.5). None of the individuals tested positive for COVID‐19. Presentations of people aged <18 years to the emergency department decreased by 27% in the pandemic period compared to the average of the pre‐pandemic periods (4799 vs 6550; range 6268 to 7131). Conclusions: A significant increase in the frequency of severe diabetic ketoacidosis at presentation of type 1 diabetes was observed during the initial period of COVID‐19 restrictions. We hypothesize that concern about presenting to hospital during a pandemic led to a delay in diagnosis. These data have important implications for advocacy of seeking healthcare for non‐pandemic‐related conditions during a global pandemic.